Cover Image. Issue 3 (12th January 2022) - Fisher, Natalie C; Loughrey, Maurice B; Coleman, Helen G; Gelbard, Melvin D; Bankhead, Peter; Dunne, Philip D
Abstract : The cover image is based on the Original Article Development of a semi‐automated method for tumour budding assessment in colorectal cancer and comparison with manual methods by Natalie C. Fisher et al., https://doi.org/10.1111/his.14574